Evaluation of the Effect of Teacher Training on the Use of Learning Technology - Meisuri, Meisuri; Siregar, Yuliza Andriyani; Halik, Abdul; Bakti, Indra; Firdaus, Mohamad (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Teachers are a profession responsible for educating, guiding, teaching, and training students. The teacher's role is important in nurturing to develop students' knowledge, attitudes, and skills. The role of teachers who provide knowledge as access to information is now aided by digital sophistication. In this case, teachers must be able to control technology for learning to students. The learning process must of course be evaluated so that the weaknesses and strengths in learning can be identified. Purpose This study aims to evaluate the effect of teacher training in the use of learning technology. This evaluation will provide an overview of the effectiveness of the training in improving teachers' understanding of learning technology. In addition, it assesses the impact that the use of technology has on student learning outcomes. Method. The method used in this research is quantitative method. Data collection is done by distributing questionnaires to teachers. Making statements related to evaluating the effect of teacher training in the use of learning technology. This statement is loaded in google from which will be processed through the SPSS application. The data obtained can be tested by proving the statements listed on Google from adjusted through facts that often occur in the world of education. Results. The results of this study suggest that evaluating the impact of teacher training can provide a basis for developing a sustainable training curriculum. The role of technology in education will change the way students learn and also the learning outcomes. This evaluation will give teachers an idea of how much students develop after the use of technology. Conclusion The conclusion of this study is that evaluation of teachers in the use of technology is also needed. Evaluation of the effect of teacher training on the use of learning technology is an assessment process to measure the extent to which training has an impact on teachers' ability to use technology. The difference in teachers' perspectives on technology also affects how much technology is used in learning. Teachers will also be a forum for the advancement of education. So that it can expand the application of technology in education.